This research Pelaksanaan Layanan Pencatatan Sipil Bagi Penyandang Disabilitas Di Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Fini Rahmatika; Jumiati Jumiati (Jurusan Ilmu Administrasi Negara, 2024)
This research is about the implementation of civil registration services for persons with disabilities at the Department of Population and Civil Registration of the City of Padang. It is important for Indonesian citizens to arrange civil registration documents, especially for persons with disabilities to obtain their needs and protect their rights so that social inequality does not occur. The method used in this research is descriptive method, qualitative approach. Field data collection through interviews, with observation (observation) and documentation to answer problems in research. The technique used in testing the validity of the triangulation technique is in the form of an analysis whose results are obtained by comparing several existing techniques and sources. Problems that arise in the Implementation of Civil Registration Services for Persons with Disabilities Disdukcapil Padang City, the provision of civil registration services does not yet have special service standards for persons with disabilities so that during the queuing process the service is still equated with services. to the general public. Behind the service standards that are not specifically made by the Disdukcapil City of Padang, the provision of accessibility is still not optimal, such as special queues for persons with disabilities and priority waiting chairs. Persons with disabilities who are also not used to accessing online civil registration services through the Sirancak application, as well as the lack of socialization from Disdukcapil in implementing the Sirancak website, in the implementation process the disabled community prefers to be served directly.